Impact of Information and Communication Technology (ICT) On the Curriculum Upgradation and Career Aspiration of Students - RASHID MANZOOR BHAT (Qubahan Academic Journal)
IT encompasses a wide range of functionalities, including communication, processing, reservations, and multimedia. Information and communication technology (ICT) or information technology and communication (ITC) refers to the primary role that communication networks perform. Modern educational systems make extensive use of ICT (information and communication technology). Because of its adaptability and the potential to foster connections among students, ICT plays a significant role in advancing academic understanding. Student interest and attitude toward their future profession or occupation is linked to their aim for a specific vocation. For students, career desire is a combination of the ability to identify and create objectives for the future, as well as to be inspired in the present toward those goals. Indigenous students are looking at a variety of options for their futures in the digital era. In the ICT industry, new technologies are continually being launched. Social Network Manager, IT Architect, Knowledge Management and Web Specialist are just few of the new ICT roles created by new technology. There are still existing job titles like "Systems Analyst," "Project Manager," and "Programmer."